Replication-Competent Variants of Human Immunodeficiency Virus Type 2 Lacking the V3 Loop Exhibit Resistance to Chemokine Receptor Antagonists - Lin, George (American Society for Microbiology, 2007)
Entry of human immunodeficiency virus type 1 (HIV-1) and HIV-2 requires interactions between the envelope glycoprotein (Env) on the virus and CD4 and a chemokine receptor, either CCR5 or CXCR4, on the cell surface. The V3 loop of the HIV gp120 glycoprotein plays a critical role in this process, determining tropism for CCR5- or CXCR4-expressing cells, but details of how V3 interacts with these receptors have not been defined. Using an iterative process of deletion mutagenesis and in vitro adaptation of infectious viruses, variants of HIV-2 were derived that could replicate without V3, either with or without a deletion of the V1/V2 variable loops. The generation of these functional but markedly minimized Envs required adaptive changes on the gp120 core and gp41 transmembrane glycoprotein. V3-deleted Envs exhibited tropism for both CCR5- and CXCR4-expressing cells, suggesting that domains on the gp120 core were mediating interactions with determinants shared by both coreceptors. Remarkably, HIV-2 Envs with V3 deletions became resistant to small-molecule inhibitors of CCR5 and CXCR4, suggesting that these drugs inhibit wild-type viruses by disrupting a specific V3 interaction with the coreceptor. This study represents a proof of concept that HIV Envs lacking V3 alone or in combination with V1/V2 that retain functional domains required for viral entry can be derived. Such minimized Envs may be useful in understanding Env function, screening for new inhibitors of gp120 core interactions with chemokine receptors, and designing novel immunogens for vaccines.